Dissolved oxygen change and freshening of Antarctic Bottom water along 62°S in the Australian-Antarctic Basin between 1995/1996 and 2012/2013. (April 2015) - Katsumata, Katsuro; Nakano, Hideyuki; Kumamoto, Yuichiro
Abstract: Significant warming and freshening signals observed in the world׳s deep oceans are generally stronger southward. In the Australian-Antarctic Basin along 62°S – near the southern edge of the western Pacific and Indian oceans – we compared water properties of Antarctic Bottom Water observed in 1995/1996 and 2012/2013. The basin collects newly ventilated dense water from the Western Pacific sector of the Antarctic coast and the Ross Sea. Compared on pressure surfaces, freshening of more than 0.003 g/kg in Absolute Salinity (0.003 in Practical Salinity Scale 1978 or PSS-78) was found below 3000 dbar. The freshening was stronger (0.02 g/kg or 0.02 in PSS-78) eastward and towards the bottom, suggesting that it originated from the regions of new bottom water production. We also detected warming ( > 0.2 ° C ) on pressure surfaces below the surface layer. Freshening of similar magnitudes were observed on density surfaces (neutral densities > 1028.1 kg / m 3 ). Adiabatic southward migration of water masses, observed by satellite altimetry, can explain the warming but not the freshening. A notable increase in dissolved oxygen on density surfaces was found near the bottom. The increase appears due to density decrease of near-bottom water, which can be explained by a change in the mixing ratio of bottom water from near the Adélie Depression (Adélie Land Bottom Water (ALBW), higher oxygen) with that from the more distant Ross Sea (Ross Sea Bottom Water (RSBW), lower oxygen): an increased contribution of ALBW and a decreased contribution of RSBW. This change might be associated with a decrease in the RSBW supply following an earlier ice-calving event in the polynya region. Oxygen rich ( > 242 μ mol / kg ) and dense ( > 1028.35 kg / m 3 ) bottom water observed in 1995/1996 in troughs near 130°E disappeared in 2012/2013, which also might reflect changes in bottom water production along the coast, possibly in Mertz and Dibble Polynyas.